1987
DOI: 10.1056/nejm198710013171401
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Corticosteroids to Alleviate Reactions to Intravenous Contrast Material

Abstract: The x-ray contrast mediums used over the past three decades have been salts of iodinated acids administered in highly hypertonic concentrations. We conducted a multiinstitutional randomized study of the protective effects of pretreatment with corticosteroids against reactions to intravenous contrast material. We gave 6763 patients two doses of oral corticosteroids (methylprednisolone, 32 mg) approximately 12 hours and 2 hours before challenge with contrast material, one dose of oral prednisolone approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
5

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(65 citation statements)
references
References 21 publications
2
58
0
5
Order By: Relevance
“…This is similar to Cohan et al's findings in their survey of the Society of Uroradiology (U. S.) [19]; however, the value of using corticosteroid prophylaxis remains contentious [20]. Lasser et al in a randomized study of 6763 patients demonstrated that corticosteroid prophylaxis reduces the incidence of all reactions to ionic contrast medium [21]. The data indicating a protective effect of corticosteroid prophylaxis when non-ionic agents are used is less secure.…”
Section: Discussionsupporting
confidence: 75%
“…This is similar to Cohan et al's findings in their survey of the Society of Uroradiology (U. S.) [19]; however, the value of using corticosteroid prophylaxis remains contentious [20]. Lasser et al in a randomized study of 6763 patients demonstrated that corticosteroid prophylaxis reduces the incidence of all reactions to ionic contrast medium [21]. The data indicating a protective effect of corticosteroid prophylaxis when non-ionic agents are used is less secure.…”
Section: Discussionsupporting
confidence: 75%
“…The prophylactic use of corticosteroids in patients at high risk of acute non-renal adverse reactions to ICM is contentious, having been recommended by some authors [2,7,17,18,19] and rejected by others [20,21]. A study conducted by Lasser et al [17] found that two doses of corticosteroid prophylaxis (32 mg methylprednisolone given orally 12 h and 2 h before contrast administration) offered a significant reduction in the incidence of all reactions to high-osmolality contrast media.…”
Section: Preventionmentioning
confidence: 99%
“…A study conducted by Lasser et al [17] found that two doses of corticosteroid prophylaxis (32 mg methylprednisolone given orally 12 h and 2 h before contrast administration) offered a significant reduction in the incidence of all reactions to high-osmolality contrast media. The study also showed that administration of steroids only at the 2 h point before contrast administration did not offer any protective effect [17]. However, in a non-randomised study by Wolf et al [20] the use of non-ionic ICM alone was significantly better in preventing occurrence of all categories of reaction than the use of ionic agents with corticosteroid prophylaxis.…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received an adapted regimen for preventing allergic reactions to the contrast media; prednisone 100 mg orally was administered before treatment and 50 mg once each on the morning of treatment and the two next days. 13 No other premedications were given routinely. If infusion-related symptoms occurred, the infusion was interrupted and diphenhydramine was administered.…”
Section: Treatment Planmentioning
confidence: 99%